2017
DOI: 10.7322/jhgd.125522
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Newborn Behavioral Observations (NBO) for the maternal care of preterm neonates

Abstract: Introduction: In the care of preterm newborn, practices that favor the participation of mothers in care are recommended. The use of appropriate instruments by professionals can contribute to strengthen maternal participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The findings from our present study and the Norwegian study [ 24 ] are also consistent with a previous randomised study of NBO delivered to selected families with at risk newborns finding no effect on the mother-infant relationship [ 25 ]. Furthermore, a qualitative study among mothers of preterm infants concluded that NBO may favour maternal understanding of the behaviour of the newborn and her participation in care [ 29 ]. In a previous paper [ 32 ], we investigated what the participating health visitors in the intervention group in the present study had learned after attending the NBO education programme and after having delivered the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our present study and the Norwegian study [ 24 ] are also consistent with a previous randomised study of NBO delivered to selected families with at risk newborns finding no effect on the mother-infant relationship [ 25 ]. Furthermore, a qualitative study among mothers of preterm infants concluded that NBO may favour maternal understanding of the behaviour of the newborn and her participation in care [ 29 ]. In a previous paper [ 32 ], we investigated what the participating health visitors in the intervention group in the present study had learned after attending the NBO education programme and after having delivered the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we found that the NBO was associated with reduced PPD symptoms in mothers of healthy term infants (Nugent, Bartlett, & Valim, 2014), while Shah (2018) reported that the NBO was effective in ameliorating maternal perinatal anxiety symptoms in a sample of women diagnosed with anxiety during pregnancy. Previous literature also suggests that the NBO promotes parents' ability to read their infant's cues (Dittz, Alves, Duarte, & Magalhães, 2017;Guimarães, Lindgren Alves, Cardoso, Penido, & de Castro Magalhães, 2017;McManus & Nugent, 2014;Simkin-Tran, Harman, & Nicolson, 2020) and improve provider confidence to work with medically fragile newborns (Kristensen, Vinter, Nickell, & Kronborg, 2019;McManus & Nugent, 2011). In a nonrandomised cluster-controlled design, Høifødt et al (2020) found that in a well-functioning, well-educated sample of mothers of full-term infants, mothers learned significantly more from the follow-up about the baby's signals and needs in relation to sleep/wake patterns, social interaction, and crying/fussiness, but the NBO was not associated with lower levels of depressive symptoms and parenting stress at 4 months postpartum.…”
Section: Relevance To the Field Of Early Childhood Mental Healthmentioning
confidence: 99%
“…In our previous work, we found that the NBO was associated with reduced PPD symptoms in mothers of healthy term infants (Nugent, Bartlett, & Valim, 2014), while Shah (2018) reported that the NBO was effective in ameliorating maternal perinatal anxiety symptoms in a sample of women diagnosed with anxiety during pregnancy. Previous literature also suggests that the NBO promotes parents’ ability to read their infant's cues (Dittz, Alves, Duarte, & Magalhães, 2017; Guimarães, Lindgren Alves, Cardoso, Penido, & de Castro Magalhães, 2017; McManus & Nugent, 2014; Simkin‐Tran, Harman, & Nicolson, 2020) and improve provider confidence to work with medically fragile newborns (Kristensen, Vinter, Nickell, & Kronborg, 2019; McManus & Nugent, 2011). In a nonrandomised cluster‐controlled design, Høifødt et al.…”
Section: Introductionmentioning
confidence: 98%
“…Pelo exposto, torna-se premente orientar as puérperas hospitalizadas, qualificando seu conhecimento acerca dos comportamentos do recém-nascido (25) e trabalhar, com elas, a construção de possibilidades para o cuidado do filho recém-nascido durante a internação na UTIN, uma vez que muitas trazem consigo expectativas acerca do que é cuidar em uma situação de nascimento saudável e a termo, sendo necessário construir, também conjuntamente, alternativas de contribuição na situação de internação na UTIN. Esse processo de construção e descoberta de novas possibilidades é que irá favorecer a sua participação no cuidado do filho e amenizar o sentimento de perda do papel materno.…”
Section: Os Desafios Enfrentados Pela Puérpera De Riscounclassified